Old habits die hard: A note on the nature of the crisis in Central Eastern Europe - Martin Raiser (Intereconomics, 1993)
In the economic literature the reasons for recession during the transformation of a planned into a market economy are still debated. The following article sets the arguments in this debate against an interpretation of the stylised facts of the transformation process in Central Eastern Europe that is centred around the legacy of soft budget constraints for state owned enterprises. It is shown that deficient bankruptcy enforcement and a perverse incentive structure at the firm level can account for adjustment inertia in emerging market economies.
Keywords: 330; System Transformation